2018
DOI: 10.1111/anu.12872
|View full text |Cite
|
Sign up to set email alerts
|

The effects of dietary astaxanthin on intestinal health of juvenile tiger puffer Takifugu rubripes in terms of antioxidative status, inflammatory response and microbiota

Abstract: A 74‐day feeding trial was conducted to evaluate the effects of dietary astaxanthin (ASTX) on antioxidative status, inflammatory response and microbiota in the intestine of tiger puffer. Four diets differed only in ASTX content, that is, 0 (Control), 50 (ASTX50), 100 (ASTX100) and 500 (ASTX500) mg/kg. Compared with Control, ASTX50 and ASTX100 significantly reduced the malondialdehyde content and spared the activities of antioxidative enzymes in hindgut; however, ASTX500 had higher activity and gene expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 64 publications
2
5
1
Order By: Relevance
“…It is estimated that trillions of microbes inhabit the gut and perform a variety of functions in animals (Dawood, 2020). In the present study, Proteobacteria was the dominant phylum in the control group, which is consistent with the research results in tiger puffer (Li et al, 2015;Ou et al, 2019;Yu et al, 2019). At the genus level, Vibrio was the dominant genus of juvenile puffer, which was similar to that of Yu et al (2019).…”
Section: The Effects Of High-lipid Diet On the Intestinal Microbiotasupporting
confidence: 90%
“…It is estimated that trillions of microbes inhabit the gut and perform a variety of functions in animals (Dawood, 2020). In the present study, Proteobacteria was the dominant phylum in the control group, which is consistent with the research results in tiger puffer (Li et al, 2015;Ou et al, 2019;Yu et al, 2019). At the genus level, Vibrio was the dominant genus of juvenile puffer, which was similar to that of Yu et al (2019).…”
Section: The Effects Of High-lipid Diet On the Intestinal Microbiotasupporting
confidence: 90%
“…The predominant genera in the intestinal bacterial community were Arcobacter , Photobacterium , Vagococcus , Weissella and Vibrio , which was different from the previous studies of pufferfish ( Talwar et al., 2018 ; Ou et al., 2019 ). Arcobacter , Photobacterium and Vibrio contains some common pathogenic species for aquatic species.…”
Section: Discussioncontrasting
confidence: 99%
“…The result was consistent with previous studies on relative abundance of Proteobacteria in fish intestinal tract with 45.5 ± 18.3% in rainbow trout (Ingerslev et al, 2014) and 59-87% in common carp (Li et al, 2013). The predominant genera in the intestinal bacterial community were Arcobacter, Photobacterium, Vagococcus, Weissella and Vibrio, which was different from the previous studies of pufferfish (Talwar et al, 2018;Ou et al, 2019). Arcobacter, Photobacterium and Vibrio contains some common pathogenic species for aquatic species.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In fact, a growing body of evidence indicates that gut microbiota plays a key role in the pathogenesis of inflammatory disorders and cardiovascular diseases, and alterations in its composition (dysbiosis) have been associated with heart failure, hypertension, atherosclerosis and metabolic syndrome (93)(94)(95). Several recent in vivo studies revealed that astaxanthin supplementation improved gut microbiota composition, which may contribute to its local and systemic anti-inflammatory and antioxidant effects (92,(96)(97)(98)(99). The beneficial effect of astaxanthin on gut microbiota has been shown to be correlated with the mitigation of cardiovascular disease-related pathologies and risk factors, such as obesity (100), insulin resistance (99) and alcoholic fatty liver disease (92).…”
Section: Antioxidant and Anti-inflammatory Mechanisms Of Action Of Astaxanthin In Cardiovascular Diseases (Review) 2 Mechanisms Of Actionmentioning
confidence: 99%